MEDICAL NEGLIGENCE CASES FROM THE PERSPECTIVE OF THE CONSUMER PROTECTION ACT 1999 - MUH. ENDRIYO SUSILA (Jurnal Media Hukum, 2012)
The presence of the Consumer Protection Act 1999 (Undang-undang Nomor 8 tahun 1999 tentang Perlindungan Konsumen) has changed the way the people look at the doctor-patient relationship. In the past, relationship between doctor and patient was only viewed as fiduciary relationship, but after the enactment of this Act some people look at it as a kind of commercial relationship. If patients were considered as consumers, any action causing damage upon the patients would subject to related legal provisions available in the Consumer Protection Act 1999. Even though claim for compensation can be carried out based on the mentioned Act however the tendency to refer to the Consumer Protection Act 1999 for settling medical negligence cases in Indonesia is still very low. It is interesting to know why the patients seem to be reluctant to employ that Act in pursuing damages. This paper will elaborate the effectiveness of the Consumer Protection Act 1999 in settling medical negligence cases in Indonesia.